Methodology of Hadith Research Critical Study of the Tradition of Criticism of Sanad and Matan Hadith - Muhyidin, Muhyidin; Nashihin, Nashihin (Research and Community Service Institute (LP2M) of Institute Pesantren Sunan Drajat, 2025)
The Hadith of the Prophet is both the basis and the second reference for Muslims, after the Qur'an. In contrast to the Quran which is textually-editorially believed to be true of Allah, this is not the case with hadith. Only the hadiths that are mutawatir are truly believed to be certainty from the Prophet, and this is also a small number. Meanwhile, other Hadiths, which are not mutawatir, which are much larger in number, still need to be studied and researched whether they are really from the Prophet or not. It is in this context that the study of criticism of the Hadith is important. If the substance of the Qur'an lies in the text or its editors alone, then in the Hadith the substance lies in the text or editor (matan) and the series of people who proclaim the text or editorial (sanad). Hadith scholars have made rules to judge a Hadith shahih (authentic) or not. On sanad for example: sanadnya must be continued, periwayat is fair, strong rote memorization, no gaffe (syadz), and no defect (illat). Whereas in matan for example: not contradicting the Quran, not contradicting other stronger Hadiths, not contradicting common sense, and historical facts. Those are the methodological steps to determine the authenticity of a Hadith. In addition, the hermeneutics approach can also be used to study hadith, as a perfection of the classical model of Hadith studies.